2019
DOI: 10.1007/s10815-019-01409-w
|View full text |Cite
|
Sign up to set email alerts
|

Human β-defensin 1 in follicular fluid and semen: impact on fertility

Abstract: Purpose β-defensins are antimicrobial peptides expressed at mucosal level of male and female genito-urinary tract, where they exert protective functions against infections, possibly preserving human health and fertility. In our study, we investigated the possible involvement of β-defensins in female and male infertility in Italian infertile couples (i) evaluating the presence of human β-defensin 1 (hBD-1) in follicular fluid (FF) and its correlation with in vitro fertilization (IVF) outcomes; (ii) investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
5
12
0
Order By: Relevance
“…In addition, it is well known that spermatozoa maintained at 37°C become exhausted especially if intracellular calcium is increased by chemical or proteins like recombinant human β‐defensin 1. These results clearly confirmed effectiveness of hBD‐1 on quality of oocyte and spermatozoa, and also improvement of sperm motility following incubation with recombinant human β‐defensin 1 (Zupin et al, ). In addition, Adria Puig‐Timonet et al () showed that adding of porcine beta‐defensins 1 and 2 to antibiotic‐free extenders for liquid‐stored boar semen could control microbial growth to some extent and did not have destructive effect on sperm viability and motility (Puig‐Timonet et al, ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition, it is well known that spermatozoa maintained at 37°C become exhausted especially if intracellular calcium is increased by chemical or proteins like recombinant human β‐defensin 1. These results clearly confirmed effectiveness of hBD‐1 on quality of oocyte and spermatozoa, and also improvement of sperm motility following incubation with recombinant human β‐defensin 1 (Zupin et al, ). In addition, Adria Puig‐Timonet et al () showed that adding of porcine beta‐defensins 1 and 2 to antibiotic‐free extenders for liquid‐stored boar semen could control microbial growth to some extent and did not have destructive effect on sperm viability and motility (Puig‐Timonet et al, ).…”
Section: Discussionsupporting
confidence: 75%
“…The results of this study are also consistent with the report by Yu et al () showing that human β‐defensin 114 in a concentration of 10–50 µg/ml can significantly rescue the sperm motility which was impaired by lipopolysaccharide during a 6‐hr incubation. Therefore, the results of present and previous studies demonstrate that sperm motility could be restored or maintained by recombinant β‐defensin 1 treatment (Zupin et al, ). Recently, Luisa Zupin et al () showed that the mean of human β‐defensin 1 in follicular fluid of women with fertilisation rate lower than 75% was significantly lower than women with fertilisation rate higher than 75%.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In bovine caudal epididymal and vas deferens epithelial cells, defensin β 126 (DEFB126) is associated with antimicrobial peptides involved in sperm motility (Fernandez‐Fuertes et al, ), cell signaling, chemoattraction, immunoregulation (Narciandi et al, ), and sperm binding to the oviductal epithelium (Lyons et al, ). In human studies, incubation of sperm with defensin improved sperm motility and pregnancy rate (Zupin et al, ). DEFB126 is important for binding of spermatozoa to the epithelia of oviduct through glycosylation and during capacitation, it facilitates sperm binding to the zona pellucida (Dorin & Barratt, ).…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%
“…The addition of cauda epididymal fluid (CEF) of cattle containing β-defensin 126 ( BBD126 ) can significantly improve the motility of bovine spermatozoa [ 9 ]. The results of some studies suggested that human β-defensin 1 ( hBD-1 ) can affect the quality of sperm and improve sperm motility when exogenously added [ 10 , 11 ]. Inhibition of the expression of Bin1b , a rat epididymis-specific β-defensin with antimicrobial activity [ 12 ], resulted in a decrease in the binding of Bin1b to sperm and a significant decrease in sperm motility and progressive movement [ 8 ].…”
Section: Introductionmentioning
confidence: 99%